Construction of the Meaning of Maulid Nabi Muhammad in the Ngabungbang Tradition at Pondok Pesantren Cikalama in Sumedang, West Java - Mukhlis Aliyudin; Enjang Enjang; Encep Dulwahab (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2022)
The tradition of celebrating the birth of the Prophet Muhammad or Maulid Nabi Muhammad, which is carried out by Muslims in various regions in Indonesia, has its own meaning, as does the tradition in Pondok Pesantren Cikalama Sumedang West Java, known as the Ngabungbang tradition. Using the phenomenological method, this study aims to uncover the construction of the meaning of those who follow the Ngabungbang tradition in the celebration of the Maulid Nabi Muhammad in Sumedang West Java. The results of the study show that there are 6 meanings in the Ngabungbang tradition. First, as a display of gratitude by the participants for the various blessings and gifts bestowed by Allah; Second, as a means to shape the soul in building and preserving brotherhood and the spirit of cooperation among Muslims; Third, as a means to increase obedience to Allah as the Creator, obedience to the Prophet who taught various good deeds for the salvation of humans in this world, and to the teachers who taught religious teachings; Fourth, to enhance belief and faith in the teachings of Islam; Fifth, as a motivation to ignite the spirit of work, leading to an increase in the level of economy; and Sixth, to attain inner peace from life’s challenges and problems. When the inner self is at peace, one’s work and activities become more focused and one’s efforts become more confident in achieving maximum results.